Energy Consumption Estimation of Organic Nonvolatile Memory Devices on a Flexible Plastic Substrate. (8th October 2015) - Jang, Jingon; Song, Younggul; Yoo, Daekyoung; Cho, Kyungjune; Kim, Youngrok; Pak, Jinsu; Min, Misook; Lee, Takhee
Abstract : The energy consumption during the operation of organic nonvolatile memory devices fabricated on a flexible polyethylene naphthalate (PEN) substrate is investigated. For bistable resistive memory devices, the applied external voltage and time are essential factors for switching the memory cell from the OFF to ON state because the amounts of voltage and time determine the applied energy needed to set the memory cell. Using the composite material polyimide (PI) and [6, 6]‐phenyl‐C61 butyric acid methyl ester (PCBM) as the active layer of the bistable resistive memory devices on a flexible PEN substrate, nonvolatile unipolar switching behavior and good electrical reliability of PI:PCBM memory devices are observed, and the relationship between the applied energy and the switching characteristics for various applied voltages and times is characterized. The results of the performed experiments show that higher ON state currents are reached as greater set voltages or times are applied, and reliable switching behavior is observed at over ≈10 −6 J of applied energy with at least 4 V of applied voltage and 10 ms of pulse time. Abstract : Energy consumption of organic nonvolatile memory devices is studied through bistable switching characteristics from the OFF to ON state by applying various set voltage and times on polyimide (PI):[6, 6]‐phenyl‐C61 butyric acid methyl ester (PCBM) memory cells. The resulting ON state current is dependent on applied energy values, which are explained by the charge‐trapping mechanism of the PI:PCBM active layer of the memory devices.